ANALISIS SENYAWA BIO AKTIF DARI EKSTRAK BUI PICUNG (Pangium edule Reinw.) SEGAR - Mangunwardoyo, Wibowo; Ismaini, Lily; Heruwati, Endang Sri (BERITA BIOLOGI, 2008)
Pangi (Pangium edule Reinw.) seed has long been used traditionally as a preservative agent for fish, especially in remote areas.A study has been conducted on analysis of bioactive compounds of pangi fresh seeds extracts and their fractions.In this study,maceration of fresh seed using water and 50% ethanol was carried out followed by thin layer chromatography (TLC) analysis to see weather the extracts contained tannin. Both extract then separated into their respective fractions using column chromatography.Fractions which had been tested to have highest antibacterial activity were then analysed using gas chromatography mass spectrometry (GC-MS) to assess the active compounds which believe to be a preservative agent.Identification of water and 50% ethanol extract of Pangium edule Reinw.fresh seeds with TLC resulted that tannin were found in those extracts. Furthermore, GC-MS analysis showed that fractions which had been previously tested to have high antibacterial activity contained 9-octadecanoic acid whith similarity index of 89%, and 1,2-benzenedicarboxylic acid whith similarity index of 94-85%.